2003
DOI: 10.1055/s-2003-38680
|View full text |Cite
|
Sign up to set email alerts
|

Regiospecific Cyclization of4-Alkoxyvinyl Trifluoro[chloro]methyl Ketones with6-Trifluoro[chloro]methyl-2-hydrazine Pyrimidines.A Convenient Method to Obtain Trifluoro[chloro]methylated2-(5-Hydroxy-5-trifluoro[chloro]methyl-4,5-dihydro-1H-Pyrazol-l-yl]-pyrimidines

Abstract: The regiospecific synthesis of a novel series of 4trifluoro[chloro]-2-(5-hydroxy-5-trifluoro[chloro]methyl-4,5-dihydro-1H-pyrazol-1-yl]-pyrimidines from the reactions of 4-alkoxy-1,1,1-trifluoro[chloro]-alk-3-en-2-ones with 6-trifluoro[chloro]methyl-2-hydrazine pyrimidines is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 4 publications
(4 reference statements)
0
3
0
Order By: Relevance
“…It is worth highlighting that products 3–6 bear a methyl sulfanyl (–SMe) moiety, which can easily be oxidized with Oxone® or m ‐chloroperbenzoic acid followed by substitution reactions (e.g., with amines to furnish 2‐aminopyrimidines). Such reactions were proven to be effective in parent compounds previously synthesized by our research group …”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…It is worth highlighting that products 3–6 bear a methyl sulfanyl (–SMe) moiety, which can easily be oxidized with Oxone® or m ‐chloroperbenzoic acid followed by substitution reactions (e.g., with amines to furnish 2‐aminopyrimidines). Such reactions were proven to be effective in parent compounds previously synthesized by our research group …”
Section: Resultsmentioning
confidence: 96%
“…Such reactions were proven to be effective in parent compounds previously synthesized by our research group. [34][35][36] At this point, it is important to mention that we could not find any reports regarding the elimination of the -CF 3 group in cyclocondensation reactions. Searching for an explanation for this observation, we found an X-ray study that showed interactions between the fluorine of fluorinated molecules and the sp-carbon of the acetonitrile (C-F•••C≡N).…”
Section: Entrymentioning
confidence: 83%
“…However, no formation of the oxidized product was observed. Taking this into account, we next attempted to use m -CPBA, which is another popular oxidizing agent for such reactions. The conditions were adapted from previous parent substrates, , and after 16 h (using CHCl 3 at r. t.), sulfone 7 was obtained in 92% yield (Scheme ).…”
Section: Resultsmentioning
confidence: 99%